2021
DOI: 10.1177/02676591211006828
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin concentrations during cardiopulmonary bypass in pediatric cardiac surgery: a prospective study

Abstract: Introduction: Few data are available regarding intraoperative plasma concentrations of vancomycin administered as prophylaxis in pediatric cardiac surgery. The aims of this study were to investigate during pediatric cardiac surgery with cardiopulmonary bypass(CPB) the attainment of the area-under-the-curve of the vancomycin serum concentrations versus time over surgery to minimum inhibitory concentration ratio(AUCintra/MIC) of 400 (mg × h)/l and/or a target concentration of 15–20 mg/l. Methods: In a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…(2) Cardiopulmonary bypass (CPB) may alter pharmacokinetics (PK) after cardiac surgery ). ( 6) Valkenburg et al showed that children after cardiac surgery with use of CPB have a lower clearance of morphine and a higher volume of distribution compared with non-cardiac surgery suggesting that children undergoing cardiac surgery with the use of CPB may need adjusted dosages of postoperative analgesics (7,8) Opioids have been associated with potential serious adverse events, such as hypotension and respiratory depression and risk for opioid tolerance and opioid withdrawal. (9) These occurrences may result in prolonged ICU-stay.…”
mentioning
confidence: 99%
“…(2) Cardiopulmonary bypass (CPB) may alter pharmacokinetics (PK) after cardiac surgery ). ( 6) Valkenburg et al showed that children after cardiac surgery with use of CPB have a lower clearance of morphine and a higher volume of distribution compared with non-cardiac surgery suggesting that children undergoing cardiac surgery with the use of CPB may need adjusted dosages of postoperative analgesics (7,8) Opioids have been associated with potential serious adverse events, such as hypotension and respiratory depression and risk for opioid tolerance and opioid withdrawal. (9) These occurrences may result in prolonged ICU-stay.…”
mentioning
confidence: 99%